Civil liabilities for false halal logo under the Consumer Protection Act 1999 - Abu Bakar, Elistina; Ahmad, Sa'odah; Kahar, Rojanah (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
By virtue of the Trade Description Act 2011 and its Orders, the position of the halal concept is strengthened and this will definitely benefit both the suppliers as well as the consumers. Nevertheless, the Act as well as the Orders are criminal in nature since they act merely to give more authority to the enforcement bodies to regulate traders. Thus, the Consumer Protection Act 1999 (CPA) should be analysed so that it will be in line with what the Trade Description Act 2011 has provided. Primarily, this paper focuses on Part II of the CPA which deals with false and misleading statements as well as Part V which scrutinize the implied guarantee relating to the supply of goods. In addition, this paper also discusses the possible suggestions for reform which include the award of non-pecuniary damages, an equitable remedy such as an injunction, an exemplary damage as well as the possibility to allow class action. Content analysis was adopted to analyse primary and secondary data. The finding revealed that there is an inadequacy of law that protects consumers on the issue of halal product, specifically, on the rights of consumers to claim compensation. This study implies that CPA should be reviewed so that it is in line with what has been provided under the the Trade Description Act 2011. An initiative also needs to be made so that it is possible to award compensation in the case of non-halal products.